Peran Corporate Social Responsibility (CSR) PT. Belfoods Indonesia dalam Meningkatkan Pemberdayaan Masyarakat Desa Sukamaju, Bogor Jawa Barat - dewayani, anggun; Tondang, Ika Sari (Jurnal Mitra Pengabdian Farmasi, 2022)
The company has a responsibility to give rights to the community around the company environment. PT. Belfoods Indonesia has Corporate Social Responsibility (CSR) as one of the ways to channel company programs in order to meet expectations and also regulations set by the government. The people of Sukamaju Village, Jonggol District, have problems with social disparities between people living in elite housing and outside. The problem of economic inequality has made one of the company's programs helping to equalize the economy of the residents by providing economic assistance in the form of business capital for Micro Small and Medium Enterprises (UMKM) and also assistance for environmental development around the Sukamaju Village area. The distributed assistance has a significant positive impact on the progress and economic development of the community around PT. Belfoods Indonesia.